VTH subthreshold hysteresis technology and temperature dependence in commercial 4H-SiC MOSFETs. (September 2018) - Asllani, Besar; Fayyaz, Asad; Castellazzi, Alberto; Morel, Hervé; Planson, Dominique
Abstract: V TH subthreshold hysteresis measured in commercially available 4H-SiC MOSFET is more pronounced in trench than in planar ones. All planar devices from different manufacturers exhibit an inverse temperature dependence, with the hysteresis amplitude reducing as the temperature increases, whereas all trench devices from different manufacturers exhibit the opposite behaviour. A physical interpretation is proposed, based on experimental evidence, which demonstrates that temperature dependence of the V TH subthreshold hysteresis is related to the technology. The findings are relevant to the ongoing discussion on SiC bespoke validation standards development and contribute important new insight. Highlights: Even though trench technology is more advanced, it is more prone to VTH hysteresis. Temperature has opposite effects on the hysteresis of planar and trench. Planar VTH hysteresis is reduced at high temperature. Trench VTH hysteresis is enhanced at high temperature. Trench devices are more prone to oxide traps (higher concentration and broader distributions of energy levels) which are closer to midgap than to valence band. Planar devices seem to have lower concentrations of oxide traps and closer to the valence band.